Library service management as an effort to cultivate students' reading interest in improving activities and learning outcomes - Hamdani Fajar Apriwulan; Akhmad Hanama; Siti Atwano Pisriwati; Deny Hadi Siswanto (Universitas Pendidikan Indonesia, 2025)
The good condition of the school library supports students' interest in reading by providing supportive services for improving students' activities and learning outcomes. This study aims to analyze the planning of library services to increase reading interest and evaluate and assess the evaluation of library services in increasing students' reading interest in SMA Muhammadiyah Mlati as part of improving activities and learning outcomes. This study uses a qualitative descriptive approach with a case study method and data analysis techniques, including data collection, condensation, data presentation, and decision-making. The study results revealed that library service planning to increase students' interest in reading includes service-based programs and habituation supported by the procurement of collections, infrastructure, and budgets. In addition, there are also circulation services with an open service system and habit-based programs implemented through the